Erratum to "On the Cauchy problem for a model equation for shallow water waves of moderate amplitude" [Nonlinear Anal. RWA 14 (5) (2013) 2022–2026]. (June 2020) - Duruk Mutlubaş, N.
Abstract: The local well-posedness for a nonlinear equation modeling the evolution of the free surface for waves of moderate amplitude in the shallow water regime was proved in Duruk Mutlubaş (2013). In this paper, we correct the mistake made in the proof of the main result and give the appropriate assumptions and corresponding results.